Analisis Pengembangan Akomodasi Wisata Homestay di Desa Kenderan, Kecamatan Tegalalang, Kabupaten Gianyar - Suwintari, I Gusti Ayu Eka; Swantari, Anita; Wirawan, Putu Eka; Jayendra, Putu Sabda; Restiawan, I Gede Ferry (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
This study aims to analyze the development of homestay tourist accommodation in Kenderan Village, Tegalalang District, Gianyar Regency. This study uses a qualitative approach. In this study, the data were analyzed and presented descriptively. The data collection used non-participant observation, structured interviews, literature studies, and document studies. The technique SWOT analysis used for data analysis. Based on the results of the research that has been done, it is evident that each homestay has strengths, weaknesses, opportunities and challenges in managing it. In general, the strength of these seven homestays is the strong family atmosphere which is characteristic of each form of homestay. Then there is a weakness of the seven homestays, namely inadequate management due to limited human resources. The existence of culture and nature that are still beautiful is an opportunity for the seven homestays in Kenderan Village. Therefore, it is necessary to utilize existing resources so that they can be used as the main factor that attracts the attention of tourists to settle down. Next, regarding the challenges, those are generally experienced by the seven homestays are increasingly fierce and growing market competition. Keywords: Homestay, Tourism Village, Management, SWOT Analysis